CORRELATION OF GLYCEMIC CONTROL WITH SEVERITY AND EXTENT OF PERIODONTAL STATUS - Shahid, Hassan; Hassan, Sadia; Faisal, Ujala (Pakistan Journal of Physiology, 2018)
Background: Diabetes is one of the main causes of periodontitis. People who do not maintain good oral hygiene or good metabolic control of their diabetes are more prone to get periodontitis especially those people who are of old age and people who have had diabetes for many years. The objectives of this study were to evaluate and correlate the extent and severity of glycaemic control with periodontal disease. Method: Sixty patients visiting the dental OPD of Isra dental college and Isra University (Diabetic OPD) from February to July 2016 were recruited. Diabetic patients who had no evidence of systemic disease other than diabetes and who had advanced periodontitis (30% or more of the teeth examined having >4 mm probing depth) were included. Glycaemic control was measured using glycated haemoglobin whereas periodontal status was measured using plaque and gingival indices according to the standard protocols. A well-designed proforma was used to record demographic characteristics, oral hygiene maintaining methods, medical history, drug history and current status of periodontium on the basis of indices i.e., gingival index and plaque index. All the readings were taken at day one and after three months. Results: Of the 60 subjects; 36 (60%) were male and 24 (40%) were female with a mean age of 48.30Â±8.718 years. There was a significant and positive correlation between glycated haemoglobin and gingival index at day one and after three months (r=0.62, p=0.001 and r=0.58 and p=0.001 respectively). However, plaque index was correlated with glycated haemoglobin only after three months (r=0.15, p=0.02). Conclusion: Glycated haemoglobin and periodontitis are positively correlated implying that diabetic control may improve periodontal status as well. Pak J Physiol 2018;14(2):28â€“30